Adverse Drug Reaction reports for cardiometabolic drugs from sub‐Saharan Africa: a study in VigiBase. Issue 6 (18th March 2015) - Berhe, Derbew Fikadu; Juhlin, Kristina; Star, Kristina; Beyene, Kidanemariam G. M.; Dheda, Mukesh; Haaijer‐Ruskamp, Flora M.; Taxis, Katja; Mol, Peter G. M.
Abstract Objective Identifying key features in individual case safety reports (ICSR) of suspected adverse drug reactions (ADRs) with cardiometabolic drugs from sub‐Saharan Africa (SSA) compared with reports from the rest of the world (RoW). Methods Reports on suspected ADRs of cardiometabolic drugs (ATC: A10[antidiabetic], B01[antithrombotics] and C[cardiovascular]) were extracted from WHO Global database, VigiBase®(1992–2013). We used vigiPoint, a logarithmic odds ratios (log2 OR)‐based method to study disproportional reporting between SSA and RoW. Case‐defining features were considered relevant if the lower limit of the 99% CI > 0.5. Results In SSA, 3773 (9%) of reported ADRs were for cardiometabolic drugs, in RoW for 18%. Of these, 79% originated from South Africa and 81% were received after 2007. Most reports were for drugs acting on the renin–angiotensin system (36% SSA & 14% RoW). Compared with RoW, reports were more often sent for patients 18–44 years old (log2 OR 0.95 [99 CI 0.80; 1.09]) or with non‐fatal outcome (log2 OR 1.16 [99 CI 1.10; 1.22]). Eight ADRs (cough, angioedema, lip swelling, face oedema, swollen tongue, throat irritation, drug ineffective and blood glucose abnormal) and seven drugs (enalapril, rosuvastatin, perindopril, vildagliptin, insulin glulisine, nifedipine and insulin lispro) were disproportionally more reported in SSA than in the RoW. Conclusions 'In recent years, the number of adverse drug reactions (ADRs) reported in Sub‐Saharan Africa (SSA) has sharply increased. The data showed the well‐known population‐based differential ADR profile of ACE inhibitors in the SSA population.'